Einstufung des Grades der Schwerbehinderung bei Kindern und Jugendlichen mit Chronischer Myeloischer Leukämie - Suttorp, Meinolf; Sembill, Stephanie; Metzler, Markus (TumorDiagnostik & Therapie, 2021)
Background CML comprises only 2-3% of all diagnosed pediatric leukemias. Mostly diagnosed in chronic phase (CML-CP), the disease progresses without treatment to accelerated phase (CML-AP) and finally to life-limiting blastic phase (CML-BP). Contrasting the therapy of other leukemia types, CML-CP is not treated by intense chemotherapy but with oral drugs -termed tyrosine kinase inhibitors (TKI)- for an unlimited duration. This therapy may be associated with general and developmentalspecific side effects. The rarity of pediatric-CML is limiting the experience in assessment of the disability rating (DR) as an administrative health authority procedure. Methods A questionnaire was sent out evaluating the procedures and results associated with the application of a disabled person's pass. Results 34 out of 70 patients (49%; median age 11 yrs., range 3-17 yrs.; CML-CP/-AP/-BP: N=28/3/3) replied to the questionnaire. Median duration of TKI therapy was 33 months (range 4-163) and associated in 71% (24/34) of the patients with side effects. 5/34 (15%) patients did not apply for a pass. DR 100 was assigned to all patients with CML-BP and to 2/3 patients with CML-AP; the 3rd patient was assigned DR 60. In the 21 patients with CML-CP the assigned DR varied from 20-100; 9/28 patients (32%) were assigned to DR 50. Special identifier label H (helpless) was assigned to 5/28 patients (18%) with CML-CP. Conclusion Compared to other pediatric malignancies, the broad range of DR in CML-CP points to unsureness when assessing the limitations exerted by the disease and its therapy. Guidelines for adults with CML offer little orientation only as pediatric patients frequently suffer from developmental-specific side effects.
Created from Fastlane, Scopus look-up
Keywords: Chronic Myeloid Leukemia; disability rating; Pediatric CML; TKI side Effects